Expert Panel Weighting and Aggregation of the Sustainable Society Index (SSI) 2010 – a Decision Analysis Approach. (3rd October 2016) - Seppälä, Jyri; Leskinen, Pekka; Myllyviita, Tanja
Abstract: A sustainable society index (SSI) has been designed to measure the sustainability of different countries in terms of economic, environmental and human well‐being dimensions. These areas were subdivided into eight categories and 24 indicators. The paper shows that the SSI could be considered as a decision‐making problem with multiple objectives. We propose a decision‐analysis approach for estimation of the weights of indicators, categories and dimensions of well‐being, with the target being a construction of overall scores for countries. A questionnaire was sent to experts from several countries, and the weights were estimated from their individual answers. The SSI 2010 results for different countries were recalculated through utilization of the estimated weights. There were some differences in the rankings compared with the earlier results with equal weights. Potential biases of the SSI approach used are critically evaluated, and opportunities to develop the SSI described. Copyright © 2016 John Wiley & Sons, Ltd and ERP Environment